Lipid droplet synthesis is limited by acetate availability in starchless mutant of Chlamydomonas reinhardtii. Issue 4 (10th January 2013) - Ramanan, Rishiram; Kim, Byung-Hyuk; Cho, Dae-Hyun; Ko, So-Ra; Oh, Hee-Mock; Kim, Hee-Sik
Abstract : Phenotypic and genotypic changes in Chlamydomonas reinhardtii BafJ5, a starchless mutant, with respect to lipid metabolism was studied in different trophic states under nitrogen (N) sufficient and limited conditions. Interestingly, cellular lipid content increased linearly with input acetate concentration with highest lipid content (∼42%) under nitrogen limitation and mixotrophic state. RT‐qPCR studies indicate that key fatty acid biosynthesis genes are down‐regulated under N limitation but not under mixotrophic state, whereas, ACS2, encoding Acetyl‐CoA synthetase, and DGTT4, encoding Diacylglycerol O ‐acyltransferase, are up‐regulated under all conditions. These results collectively indicate that acetate is the limiting factor and central molecule in lipid droplet synthesis. The study also provides further evidence of the presence of a chloroplast pathway for triacylglycerol synthesis in microalgae. Abstract : ► Lipid droplets increase linearly with input acetate concentration. ► Maximum lipid content under mixotrophy & N limitation. ► ACS2 & DGTT4 genes are up‐regulated whereas FA synthesis genes are downregulated. ► Further evidence of chloroplast pathway for TAG synthesis in algae. ► Acetate is the central molecule in LD synthesis in Chlamydomonas reinhardtii .